GREENHOUSE GASES EMISSION INVENTORY OF POLLUTANT CO2 AND CH4 FROM TRANSPORTATION USING VEHICLES DISTANCE TRAVELLED AND FUEL CONSUMPTION ACCORDING TO AIR QUALITY MANAGEMENT IN BANDUNG CITY AND REGENCY - LEOPOLD S.M. SIHOMBING, ADOLF
Emission inventory can used as tool to make policy decision included air pollution problem. Inventory intended to identify emitter contributions concern to carbon dioxide and methane concentration in city and Bandung regency. The study confined by transportation sector that divide based on the type of vehicles existing in Bandung (passenger car, light duty vehicles, heavy-duty vehicles and motorcycle). The calculation of greenhouse emission loading had done by two approaches using vehicles distance travelled and fuel consumption includes gasoline and diesel. The result show that the emission level of CO2 was increased 24.13% and 39.41% for CH4 during 2004 until 2006. The main sources of CO2 and CH4 were bus (1447218.2 tons/year) and motorcycle (922.06 tons/year). The result showed that the level of CO2 concentration based on vehicles distance travelled approach was 3130874.65 tons in 2004, 3276853.3 tons in 2005 and 3886394.94 tons in 2006. Based from the fuel consumption approach, the concentration of CO2 was 1370261.42 tons in 2004, 1694919.43 tons in 2005 and 1667906 tons in 2006. The level concentration of CH4 based on vehicles distance travelled was 972.38 tons in 2004, 1066.09 tons in 2005 and 1355.63 tons in 2006, while its concentration based on fuel consumption was 536.18 tons in 2004, 645.61 tons in 2005 and 582.35 tons in 2006. A certain intervals of calculation was been caused by type of vehicles that consumed its fossil fuel out of study area. The increasing of unit transportation without increasing the fuel quota in 2006 was caused differences value in calculation.